The Effect of Self-Efficacy and Well-Being on Smartphone Addiction - Nurussanatil Alfaini; Nurussakinah Daulay (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Teenagers today are very enthusiastic about using smartphones, whether they are used for learning or playing online games. This makes teenagers more susceptible to smartphone addiction (smartphone addiction). The purpose of this study was to determine the role of self-efficacy and well-being on the tendency of students to experience smartphone addiction. The subjects in this study were 202 students of MTs Nurul Islam Indonesia using quantitative methods. The data analysis technique used in the form of multiple linear regression analysis using SPSS 23 software. The results of this study indicate that there is an influence between self-efficacy and well-being on smartphone addiction (F = 10.164) and 9.3% while the remaining 90.7% is influenced by other factors. which were not included in the study.